Frequency of Chemical Burn and Mortality Rate in Admitted Patients at a Tertiary Care Hospital of Karachi (Medical Forum Monthly, 2024)
Background: Developing countries have a high incidence of burn injuries creating a fear or respect public health problem. Acid assault is one of the most savagely violent of crime which aims to punish the victim or to destroy the victim’s social life. This violent usually occurs in third world countries like Pakistan, Bangladesh, and Iran etc. In Pakistan 7 to 17 burn admissions annually recorded during the study period.Objectives: To assess the epidemiological factors in terms of incidence morbidity and mortality and the effect of social and cultural issues associated with the chemical burns.Study Design: A cross sectional retrospectivePlace and Duration of Study: This study was conducted in burns ward of Civil Hospital Karachi from May 2004 to Oct 2010.Materials and Methods: All the patients were identified the etiology and the extent of damage that was produced as a result of throwing corrosive chemicals.Results: Overall 127 patients record were included in study. It was more commonly found in younger age group i.e. 21 -30 years. The incidence was much more in males (74.0 %) as well as stratified by age. Majority of the patients (90.6%) were burn with Accidental. Moreover, the patients who had 3RD degree burn (41.9%) that leads to more mortality in our circumstances. Septicemia was the leading cause of death. The burn injury was significantly associated with degree of burn, depth, extent and mode of injury. The most common incidence found was accidental followed by assault.Conclusion: Lack of information about the catastrophic outcome of this action plus the wide spread availability of strong destructive chemicals are the main reasons for the rising incidence of this crime. The majority of deep burns were on homicidal. So measure should be taken to generate awareness for protective measures, immediate first aid, proper professional treatment, restriction in availability of acid, implementation in the existing law regarding the bail of accused etc to prevent these accidents and ensure safety.